Assessment of depression in diabetic patients - Kotwal, Shivwani D.; Kour, Navneet; Gadda, Irfan R.; Devraj, (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes is one of the most common chronic conditions in the world. The worldwide prevalence of diabetes mellitus (DM) has risen dramatically over the past two decades because of increasing obesity and reduced activity levels. The purpose of this study was to show the association between depression and diabetes. Methods: It was a cross-study. The study included 240 patients who were chosen randomly with no gender bias. A convenient subject of 240 diabetic patients was interviewed. Results: Out of the total 240 diabetic patients, included in this study, the majority of patients, 52.63% in the age group of 60 years had depression with a Hamilton score of >19 while 47.37% of patients in the age of 40 to 50 years had Hamilton score of >19. 84.21% of males had depression with a Hamilton score >19 as compared to females who had a Hamilton score of 15.79%. The patients within the age group of 40-59 have 2.5 times more risk of having depression as compared to the age group of 20 to 39 and patients in the age group >60 years have 4.23 times higher risk of depression as compared to patients in the age group of 20 to 39 years. The association between gender and depression shows that males have a higher rate of depression (78.17%) as compared to females (21.81%) with an odd's ratio of 3.0. Conclusions: Our study showed a high prevalence of depression and anxiety in male patients and the elderly age group. Planning and implementation of screening for mental health issues in the elderly population diagnosed with a lifestyle disease-such as type 2 diabetes mellitus-with existing comorbidities should be recognized as one of the most important goals of the public health system. It seems necessary to involve medical teams in the screening process to verify the symptoms, promptly establish the diagnosis, and initiate the appropriate depression treatment. In diabetic patients, depression remains underdiagnosed and an important aspect of the diabetic specialists would be the awareness of this quite common co-morbidity.